2017
DOI: 10.1007/s00441-016-2563-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibiting MMP13 and ADAMTS5 by intra-articular injection of small interfering RNA in a surgically induced osteoarthritis model of mice

Abstract: Matrix metalloproteinase 13 (MMP13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) are thought to play critical roles in cartilage degradation at the early phase of osteoarthritis (OA). The aim of this study is to examine the effect of chemically modified Mmp13 or Adamts5 small interfering RNA (siRNA), alone or in combination, in a mouse OA model. OA pathology was surgically induced in 9-week-old male C57/BL6 mice (n = 64) via destabilization of the medial meniscus (DMM). We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…ECM degradation, which characterizes osteoarthritis, is promoted by several protein-degrading enzymes, including matrix metalloproteinases (MMPs), particularly MMP3 and MMP13 710 , and members of the a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) family such as ADAMTS4 and ADAMTS5 1116 . Hypoxia inducible factor 2 (HIF2) also reportedly acts as an upstream regulator of osteoarthritis inducible factors 1719 .…”
Section: Introductionmentioning
confidence: 99%
“…ECM degradation, which characterizes osteoarthritis, is promoted by several protein-degrading enzymes, including matrix metalloproteinases (MMPs), particularly MMP3 and MMP13 710 , and members of the a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) family such as ADAMTS4 and ADAMTS5 1116 . Hypoxia inducible factor 2 (HIF2) also reportedly acts as an upstream regulator of osteoarthritis inducible factors 1719 .…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions in extracellular matrix (ECM) homeostasis are key events in the pathogenesis of OA (25) and ADAMTS5 has a key role in ECM homeostasis due to its capacity to degrade a wide range of ECM components (26). The current study demonstrated that the expression of miR-27a-3p was significantly lower in OA cartilage compared with normal cartilage, while the overexpression of miR-27a-3p in human chondrocytes inhibited ADAMTS5 expression.…”
Section: Discussionmentioning
confidence: 58%
“…A relevant effect of NAPA is the modulation of ADAMTS5, the foremost cartilage ECM-degrading enzyme responsible for aggrecan removal in the early phase of the disease 56 . This pivotal role is confirmed by the effectiveness of inhibiting OA progression by a treatment of this catabolic enzyme by small interfering RNA 56 .…”
Section: Discussionmentioning
confidence: 99%
“…A relevant effect of NAPA is the modulation of ADAMTS5, the foremost cartilage ECM-degrading enzyme responsible for aggrecan removal in the early phase of the disease 56 . This pivotal role is confirmed by the effectiveness of inhibiting OA progression by a treatment of this catabolic enzyme by small interfering RNA 56 . Notably, ADAMTS5 is an OA drug target validated with the DMM model 31 , and indeed, its antibody-mediated neutralization has proven able to inhibit OA progression in a DMM model 57 .…”
Section: Discussionmentioning
confidence: 99%